A strategic-relational approach to analyzing industrial policy regimes within global production networks: The Ethiopian Leather and Leather Products Sector - Jan Grumiller (Austrian Foundation for Development Research (ÖFSE), 2019)
This paper contributes to debates regarding the lack of theorization of the state and the overemphasis on lead firms in studies of global value chains (GVCs) and global production networks (GPNs). This paper combines the GVC/GPN frameworks with a strategic-relational approach (SRA), a SRA conceptualization of the developmental state, and literature about the embeddedness of firms. Empirically, the paper analyzes the conflictual relationship between firms and the state's strategies that structure and re-structure the development, industrial policy regime, and GVC/GPN integration of the Ethiopian leather and leather products (LLP) industry.
Keywords: 330; global value chains; developmental state; embedded autonomy; network embeddedness